Exploring Factors Behind Offline and Online Selfie Popularity Among Youth in India - Srivastava, Sanchita; Upadhaya, Puja; Sharma, Shruti; Gupta, Kaveri (Frontiers in Psychology, 2018)
“The Selfie Culture”, practiced globally, is gaining popularity with each passing day. Owing to its ubiquitous fame across the globe, it becomes essential to inquire the grounds for such worldwide recognition. In few years, it also became the centre of attraction among researchers and previous studies had recognized two important aspects of selfie: first, why is selfie posting on social media is increasing day by day and second, who choose to involve more frequently in selfie posting behavior on social media? However, these studies focused only on its online popularity on various social media platforms but did not pay much attention on its offline popularity among selfie takers. In addition to this, the multifaceted sides of selfie which may make it different from other pictures and might also play an important role in its popularity in both offline and online platforms remained unexplored. The present study addressed this gap and explored two important aspects of selfie related behavior, First, it emphasized the significance of understanding the user’s conception of selfie and second, it explored the determining factors behind both offline (taking) and online (posting) modes of the practice. 60 college going students (44 females & 16 males) living in Delhi, India participated in the study. Semi-structured interviews were conducted and qualitative thematic analysis was used to cull out the themes. The results showed five factors (looks good, keeping memories, mood driven, mirroring the self and posting on social media) behind selfie offline (taking) involvement. Further, the online (posting) selfie popularity had been driven by three factors (social approval, being the best among the rest, to maintain online presence). Participants' popularity of selfie usage in both offline and online modes advocates the need to explore the offline selfie involvement of selfie takers in future research. The study also extended the existing conceptualization of selfie phenomenon which could help to unravel its wide popularity among its users.